Capacity building of private sector workforce for public health services in India: Scope and challenges - Sembagamuthu Sembiah; Bobby Paul; Aparajita Dasgupta; Lina Bandyopadhyay (Wolters Kluwer Medknow Publications, 2018)
Indian health sector is a complex admixture of public and private providers, but several lacunae of public health service delivery system in terms of human resource, access, and quality have resulted in unprecedented growth of private sector. Although seamless delivery of services at rural and urban areas, timely approach, and improved information technology system are the strength of the private sector, this package comes at the cost of high out-of-pocket expenditure. Mobilization of private sector health workforce by their capacity building in terms of orientation toward public health services is one of the available solutions to move toward wider coverage of public health services. However, numerous challenges need to be addressed before realization of this vision.